Correlationship Between Social Responsibility And Sense Of Nationalism Of Teacher Trainee Students- A Study (Journal of Namibian Studies : History Politics Culture, 2023)
The study aimed to find out the level of social responsibility and sense of nationalism among teacher trainee students and the relationship between the two. The survey method was used to collect and analyze data from a large number of respondents. The results showed that the majority of teacher trainee students had a high level of social responsibility and sense of nationalism. Furthermore, there was a positive correlation between social responsibility and sense of nationalism among teacher trainee students. The study concludes that teachers can play a significant role in promoting social responsibility and sense of nationalism among teacher trainee students, which can lead to a better future for society.